INFORMATION TECHNOLOGIES IN ENDOCRINOLOGY: ENHANCING DIAGNOSIS, TREATMENT, AND PATIENT MANAGEMENT - Ermatova Dilnozaxon Shuxratovna; Ismanova Arofatxon Abduldulhamidovna (TADQIQOTLAR, 2025)
Abstract. Information technologies (IT) have significantly transformed the field of endocrinology by enhancing diagnostic accuracy, personalizing treatment plans, and improving  patient  management.  The  integration  of  AI,  big  data,  electronic  health records  (EHRs),  and  telemedicine  has  revolutionized  the  way  endocrinologists diagnose  and  treat  endocrine  disorders  such  as  diabetes,  thyroid  diseases,  and metabolic  disorders.  This  article  explores  the  role  of  information  technologies  in endocrinology,  emphasizing  their  impact  on  diagnostics,  treatment  personalization, and  remote  patient  management.  It  also  discusses  the  challenges  and  ethical considerations related to data security and AI usage. As IT continues to evolve, its integration into endocrinology is expected to improve patient outcomes and foster more efficient and personalized healthcare.